La médiation de l’archéologie. Éthique de la complaisance ou impératif épistémologique ? - Marc-Antoine Kaeser (In Situ)
The importance of archaeological mediation is now recognized throughout the archaeological discipline. Yet, involvement in this field often rests on circumstantial incentive and purely formal motives which in some cases betray a certain complacent expediency of conforming to “political correctness”. Though the development of cultural mediation must indeed offset certain perverse effects of the professionalization of the discipline and respond to challenges that have arisen following the emergence of a new public perception of cultural heritage, advocating for mediation exceeds image-related concerns and clearly goes beyond socio-political, cultural and societal interests. Indeed, cultural mediation must subscribe to a holistic conception of the archaeological approach, in which mediation is a part of the heuristic function. This is in response to a specificity of archaeology – an undertaking that destroys its object as the latter is progressively revealed. During the elimination mechanism inherent to archaeological reasoning and excavation, archaeologists are indeed confronted with mediational imperatives constituting needs that must also fuel their thought process beforehand. In this sense, mediation constitutes a true epistemological requirement, the legitimacy of which lies close to the heart of archeological research.